COMPARATIVE BATTERY EFFICIENCY ANALYSIS FOR HYBRID ELECTRIC VEHICLES BASED ON MATLAB MODELLING - Nicolaica Mihai-Ovidiu; Tarniceriu Daniela (European Scientific Journal, ESJ, 2015)
The present paper introduces a new comparative analysis method that is applied on different hev battery types, with the scope of enhancing the energy efficiency. The research is based on matlab modeling and hardware in the loop approach. The study considers a set of critical parameters that influence the system performance. The added value is given by the comparative overview as a result of the applied analysis. This method identifies also the set of parameter values needed for a better performance that can be afterwards considered in developing future battery types. A set of 4 case studies are proposed and the efficiency of the analysis method is proven through a series of simulation results. The motivation of the research is given by the fact that the battery is one of the most important components in hybrid electric vehicles architecture. A good understanding of different battery behavior helps in using the best suited battery system for a certain architecture resulting in a better control strategy, better energy efficiency and better costs. The advantage of this method is that the battery performance can be assessed in an early stage of development. The results contribute to the practical need of developing new battery control systems at higher quality standards.